The impact of user fee removal policies on household out-of-pocket spending: evidence against the inverse equity hypothesis from a population based study in Burkina Faso - Ridde, Valéry; Agier, Isabelle; Jahn, Albrecht; Müller, Olaf; Tiendrebéogo, Justin; Yé, Maurice; De Allegri, Manuela (The European journal of health economics, 2015)
User fee removal policies have been extensively evaluated in relation to their impact on access to care, but rarely, and mostly poorly, in relation to their impact on household out-of-pocket (OOP) spending. This paucity of evidence is surprising given that reduction in household economic burden is an explicit aim for such policies. Our study assessed the equity impact on household OOP spending for facility-based delivery of the user fee reduction policy implemented in Burkina Faso since 2007 (i.e. subsidised price set at 900 Communauté Financière Africaine francs (CFA) for all, but free for the poorest). Taking into account the challengeslinked to implementing exemption policies, we aimed to test the hypothesis that the user fee reductionpolicy had favoured the least poor more than the poor.
Published online: 12 January 2014
Gesehen am 18.06.2020